Disparitas Sanksi dalam Putusan Dewan Kehormatan Penyelenggara Pemilu Nomor 25-PKE-DKPP/I/2025 terhadap Anggota Komisi Pemilihan Umum Kota Banjarbaru - Renaldy Farhan; Deden Koswara (Lembaga Yasin AlSys, 2026)
Although the enforcement of the code of ethics for election organizers by the Election Organizer Honorary Council (DKPP) has received attention in various previous studies, studies that specifically examine disparities in sanctions within a single decision against subjects involved in the same legal event remain limited. This study aims to analyze the ratio decidendi of the DKPP in imposing disparities in sanctions on members of the Banjarbaru City General Election Commission (KPU) in Decision No. 25-PKE-DKPP/I/2025 and to assess its conformity with the principle of proportionality in law. This study uses a normative legal method with statutory, case, and conceptual approaches. Data were collected through a literature study of laws and regulations, DKPP decisions, legal literature, and previous research findings, and were then analyzed descriptively and analytically. The results show that the DKPP differentiated sanctions based on the corrective attitude demonstrated by one of the respondents. However, this consideration was not accompanied by clear parameters regarding the weighting of the degree of fault, role, and form of responsibility of each respondent. As a result, the disparity in sanctions imposed still leaves issues in terms of proportionality, legal certainty, and consistency in enforcing the code of ethics. This finding contributes to the development of studies on election law and ethical adjudication, particularly regarding the application of the principle of proportionality in the imposition of sanctions. The implications of this study can serve as evaluation material for the DKPP in formulating legal considerations that are more transparent, measurable, and accountable, while also opening space for further research on the consistency of disparities in sanctions across various DKPP decisions.